Flexible laminate
By using perfluorocopolymer matrix and L-glass fabric in metal-covered laminates, combined with conductive plating, the problem of high dielectric constant and dissipation factor in high-frequency applications is solved, and low dielectric constant and low dissipation factor is achieved laminate, suitable for high-frequency applications such as 5G communication networks.
Patent Information
- Application Number
- CN202380039902.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-19
- Filing Date
- 2023-07-05
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing metal-covered laminates have problems with high dielectric constant and dissipation factors in high-frequency applications, which are difficult to meet the needs of high-frequency applications such as 5G communication networks.
The perfluorinated copolymer matrix is used as the dielectric substrate, and the L-glass fabric is embedded, and the conductive plating layer is installed on its surface. By adjusting the ratio of fluorinated and non-fluorinated perfluorinated copolymers and the number of carboxyl end groups, the dielectric constant and The dissipation factor increases the adhesion between the conductive plating layer and the dielectric substrate, and prevents the formation of conductive anode wires.
The metal-covered laminate with low dielectric constant and low dissipation factor is achieved, suitable for high-frequency applications, providing better dimensional stability and electrical reliability, and avoiding the formation of conductive anode wires.
Smart Images

Figure CN119212860A_ABST
Abstract
Description
Background Art
[0001] Metal clad laminates are used as printed wiring board substrates in a variety of electronic device applications. Summary of the invention
[0002] In one aspect, a laminate includes a dielectric substrate comprising a perfluoro copolymer matrix comprising a fluorinated perfluoro copolymer and a non-fluorinated perfluoro copolymer; an L-glass fabric embedded in the perfluoro copolymer matrix; and an additive material dispersed in the perfluoro copolymer matrix, wherein the additive material is capable of absorbing ultraviolet light; and a conductive coating disposed on a surface of the dielectric substrate.
[0003] Implementations may include any combination of one or two or more of the following features.
[0004] L-glass fabrics contain yarns of L-glass, NL-glass or L2-glass.
[0005] The laminate has a thickness of 20 μm to 200 μm, for example 30 μm to 90 μm or 30 μm to 60 μm.
[0006] The dielectric substrate has a dielectric constant of 2.10 to 2.70, such as 2.10 to 2.40 at 10 GHz.
[0007] The dielectric substrate has a thermal coefficient of dielectric constant having a value of -250 ppm / °C to +50 ppm / °C in a temperature range of 0°C to 100°C.
[0008] The dielectric substrate has a dissipation factor at 10 GHz of less than 0.0015, eg, 0.0006 to 0.001 or 0.0006 to 0.0008.
[0009] The laminate has a planar shape defining an XY plane, and wherein a thermal expansion coefficient of the laminate in the XY plane is 5 ppm / °C to 25 ppm / °C, for example, 14 ppm / °C to 20 ppm / °C or 16 ppm / °C to 22 ppm / °C.
[0010] The fluorinated perfluoro copolymers include fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and wherein the non-fluorinated perfluoro copolymers include non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers.
[0011] The perfluorocopolymer matrix comprises 50 weight percent to 90 weight percent of a fluorinated perfluorocopolymer, such as 10 weight percent to 50 weight percent of a non-fluorinated perfluorocopolymer.
[0012] The number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix is sufficient to render the laminate free of conductive anodic filaments (CAFs).
[0013] The number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix provides the laminate with a peel strength between the dielectric substrate and the conductive coating greater than 2 pounds per inch.
[0014] The number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix is from 30 to 70.
[0015] The fluorinated perfluorocopolymer has 5 or fewer carboxyl end groups per million carbon atoms.
[0016] The non-fluorinated perfluorocopolymer has from 100 to 300 carboxyl end groups per million carbon atoms.
[0017] The perfluorocopolymer matrix has a melt flow rate (MFR) of 10 to 30 g / 10 min.
[0018] The perfluorocopolymer matrix has a solder float resistance of at least 10 seconds at 288°C.
[0019] L-glass has a basis weight of less than 100 g / m2, such as less than 50 g / m2.
[0020] The L-glass fabric has a thickness of 10 μm to 100 μm, for example, 10 μm to 30 μm.
[0021] L-glass fabrics include aminosilane or methacrylate silane surface chemistry treatments.
[0022] The L-glass fabric includes a plasma-treated or corona-treated L-glass fabric.
[0023] The L-glass fabric was impregnated with a fluoropolymer.
[0024] The L-glass fabric includes a fluoropolymer coating.
[0025] Prior to incorporation into the laminate, the L-glass fabric was pretreated with a fluoropolymer treatment.
[0026] The dielectric substrate comprises 5 volume percent to 20 volume percent of L-glass fabric and 80 volume percent to 95 volume percent of a perfluoro copolymer matrix.
[0027] The water contact angle of L-glass fabric is 0° to 60°.
[0028] Additive materials include inorganic particles such as particles of cerium oxide, titanium dioxide, silicon dioxide, barium titanate, calcium titanate, or zinc oxide.
[0029] Additive materials include thermosetting polymers.
[0030] The additive material is present in the perfluorocopolymer matrix at a volume percentage of less than 2%.
[0031] The additive material is uniformly dispersed throughout the perfluorocopolymer matrix.
[0032] Conductive plating is disposed on two opposing surfaces of the dielectric substrate.
[0033] The conductive plating layer includes copper foil. In some cases, the copper foil is disposed on the surface of the dielectric substrate through a lamination process.
[0034] The conductive plating layer has a thickness of less than 72 μm, for example, 5 μm to 18 μm.
[0035] The conductive coating has a root mean square (RMS) roughness of less than 1 μm, such as less than 0.5 μm.
[0036] In one aspect, a printed wiring board includes a laminate having any one of the aforementioned features, wherein a conductor pattern is formed in the conductive plating layer.
[0037] Implementations may include any combination of one or two or more of the following features.
[0038] A through hole is defined through the thickness of the laminate; and includes a copper film that plates the through hole.
[0039] In one aspect, a multilayer printed wiring board includes a multilayer laminate structure including a plurality of printed wiring boards according to the aforementioned aspect.
[0040] Implementations may include any combination of one or two or more of the following features.
[0041] The multilayer printed wiring board includes a thermoplastic adhesive disposed between adjacent printed wiring boards in a laminated structure. In some cases, the thermoplastic adhesive bonds at a temperature of 0°C to 200°C below the melting point of the perfluorocopolymer matrix. In some cases, the thermoplastic adhesive bonds at a temperature of 0°C to 50°C below the melting point of the perfluorocopolymer matrix.
[0042] The multilayer printed wiring board includes a thermosetting adhesive disposed between adjacent printed wiring boards in a laminated structure. In some cases, the thermosetting adhesive is cured at a temperature of 150°C to 250°C.
[0043] A through hole is defined that passes through at least a portion of the thickness of the multilayer printed wiring board; and a copper film is included to plate the through hole.
[0044] An antenna capable of being used with a 5G communication network may include a printed wiring board according to the aforementioned aspect.
[0045] In one aspect, a method of manufacturing a multilayer printed wiring board includes forming a conductor pattern in a conductive plating layer of each of a plurality of laminates having any of the aforementioned features to form a corresponding printed wiring board; and laminating the plurality of printed wiring boards to form a multilayer laminate structure.
[0046] Implementations may include any combination of one or two or more of the following features.
[0047] Laminating a plurality of printed wiring boards includes using a thermoplastic adhesive to adhere adjacent printed wiring boards. In some cases, the method includes bonding the thermoplastic adhesive at a temperature of 0°C to 200°C below the melting point of the perfluorocopolymer matrix. In some cases, the method includes bonding the thermoplastic adhesive at a temperature of 0°C to 50°C below the melting point of the perfluorocopolymer matrix.
[0048] Laminating a plurality of printed wiring boards includes using a thermosetting adhesive to adhere adjacent printed wiring boards. In some cases, the method includes curing the thermosetting adhesive at a temperature of 150°C to 250°C.
[0049] The method includes defining a through hole through at least a portion of a thickness of the multilayer laminate structure. In some cases, the method includes defining the through hole in an ultraviolet laser drilling process.
[0050] In one aspect, a method of making a laminated article includes forming a layered article comprising: a first polymer film and a second polymer film, each film comprising: a perfluoro copolymer matrix comprising a fluorinated perfluoro copolymer and a non-fluorinated perfluoro copolymer, and an additive material capable of absorbing ultraviolet light; an L-glass fabric disposed between the first polymer film and the second polymer film; and a conductive coating disposed in contact with the first film; and applying heat and pressure to the layered article to form the laminated article.
[0051] Implementations may include any combination of one or two or more of the following features.
[0052] Fluorinated perfluoro copolymers include fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and non-fluorinated perfluoro copolymers include non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers.
[0053] Applying heat and pressure to the layered article includes compressing the layered article in a heated press plate.
[0054] Applying heat and pressure to the layered article includes processing the layered article in a roll-to-roll lamination process.
[0055] Applying heat and pressure to the layered article includes applying a temperature to the layered article that is 10°C to 30°C above the melting point of the perfluorocopolymer matrix.
[0056] Applying heat and pressure to the layered article includes applying a temperature of 300°C to 400°C to the layered article.
[0057] Applying heat and pressure to the layered article includes applying a pressure of 200 psi to 1000 psi to the layered article.
[0058] The method includes forming a first film and a second film in a melt processing and extrusion process. In some cases, forming the first film and the second film includes mixing a fluorinated perfluoro copolymer and a non-fluorinated perfluoro copolymer. In some cases, the method includes dispersing an additive material in the fluorinated perfluoro copolymer before mixing the fluorinated perfluoro copolymer and the non-fluorinated perfluoro copolymer.
[0059] The method includes treating the L-glass fabric with a fluoropolymer treatment. In some cases, treating the L-glass fabric with a fluoropolymer treatment includes coating the L-glass fabric with a fluoropolymer coating. In some cases, coating the L-glass fabric with a fluoropolymer coating includes coating the L-glass fabric in a solution coating process. In some cases, coating the L-glass fabric with a fluoropolymer coating includes depositing fluoropolymer particles on a surface of the L-glass fabric.
[0060] Each polymer film includes a first layer and a second layer, the first layer comprising a fluorinated perfluoro copolymer and a non-fluorinated perfluoro copolymer, the second layer comprising a non-fluorinated perfluoro copolymer, and wherein each second layer is disposed in contact with the quartz fabric, and each second layer is disposed in contact with the conductive plating layer. The details of one or more embodiments are set forth in the accompanying drawings and the following description. Other features and advantages will be apparent from the description and drawings, and from the claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 is a diagram of a flexible metal-clad laminate.
[0062] Figure 2 is a diagram of the layered structure of a flexible metal-clad laminate.
[0063] Figure 3A and Figure 3B is an illustration of a laminate having conductive anodic filaments.
[0064] Figure 4 and Figure 5 It is a diagram of a printed circuit board.
[0065] Figure 6 It is a diagram of a communication network.
[0066] Figure 7 It is a diagram of the roll-to-roll lamination process.
[0067] Figure 8 is a flow chart of a method of manufacturing a flexible metal clad laminate.
[0068] Fig. 9 is a photo of a flexible copper-clad laminate.
[0069] Fig.10 is a chart of the thickness of various flexible copper clad laminates.
[0070] Fig.11 is a chart of the resin content of various flexible copper clad laminates.
[0071] Fig. 12A and Fig. 12B is a graph of the dimensional stability measurements of various flexible copper clad laminates.
[0072] Fig.13 is a chart of the flatness of various flexible copper-clad laminates.
[0073] Fig.14 is a chart of the thickness of various flexible copper clad laminates.
[0074] Fig.15 is a chart of the resin content of various flexible copper clad laminates.
[0075] Fig.16 is a graph of the dielectric constants of various flexible copper-clad laminates.
[0076] Fig.17 is a graph of the dissipation factors of various flexible copper-clad laminates.
[0077] Fig.18A and Fig.18B is a graph of the dimensional stability measurements of various flexible copper clad laminates.
[0078] Fig.19 is a graph of the dissipation factor of the blended PFA membrane as a function of the number of carboxyl end groups per 106 carbon atoms in the membrane.
[0079] Fig. 20 is a graph of the dissipation factor of the laminate as a function of the number of carboxyl end groups per 106 carbon atoms in the blended PFA film.
[0080] Fig.21 is a graph of the copper peel strength of the laminate as a function of the number of carboxyl end groups per 106 carbon atoms in the blended PFA film. DETAILED DESCRIPTION
[0081] We describe herein a metal-clad flexible laminate having a low dielectric constant and low dissipation at high frequencies (e.g., 10 GHz). The flexible laminate described herein can be used as a substrate for printed circuit boards in high-frequency applications, such as antennas for use in 5G cellular communication networks or with automotive radars, and other applications. The flexible laminate described herein includes a dielectric substrate formed by a perfluoro copolymer matrix having an L-glass fabric embedded therein, such as a woven L-glass fabric. The perfluoro copolymer matrix contains fully fluorinated perfluoro copolymers (referred to herein as "fluorinated perfluoro copolymers") and incompletely fluorinated perfluoro copolymers (referred to herein as "non-fluorinated perfluoro copolymers"), such as fully fluorinated and incompletely fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers. The additive material in the dielectric substrate is capable of absorbing ultraviolet light, so that the laminate can be drilled with an ultraviolet laser, for example, for forming through holes through the thickness of the laminate. The flexible laminate is coated with a conductive coating, such as copper foil, on one or both sides.
[0082] The presence of the L-glass fabric results in a laminate having a high degree of planarity, e.g., the planarity is sufficient to enable alignment between multiple layers of the laminate during the drilling process. For example, in a multi-layer laminate structure, the high degree of planarity enables alignment during drilling of vias through the thickness of the multi-layer structure. Without being bound by theory, it is believed that the difference between the coefficient of thermal expansion (CTE) of the L-glass fabric and the CTE of the perfluorocopolymer matrix, as well as the relatively low modulus of the L-glass fabric (e.g., compared to quartz fabric), causes the contraction of the L-glass fabric during cooling of the laminate to be small enough to avoid generating ripples in the laminate.
[0083] refer to Figure 1 , the metal-clad flexible laminate 100 includes a dielectric substrate 102 and a conductive coating, such as metal (e.g., copper) foils 104a, 104b (collectively referred to as the conductive coating 104) disposed on the top surface 106a and the bottom surface 106b of the dielectric substrate 102, respectively. Figure 1 The conductive plating 104 is present on both surfaces 106 a , 106 b of the dielectric substrate 102 , but in some examples, the conductive plating is only disposed on a single surface of the dielectric substrate 102 (eg, only the top surface 106 a ).
[0084] The dielectric substrate 102 of the flexible laminate 100 includes an L-glass fabric 108, such as a woven L-glass fabric (e.g., L-glass, NL-glass, or L2-glass yarns woven into the fabric), embedded in a perfluoro copolymer matrix 110, the perfluoro copolymer matrix containing fluorinated perfluoro copolymers and non-fluorinated perfluoro copolymers, such as fluorinated and non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers. As discussed further below, the perfluoro copolymer matrix 110 provides a low dielectric constant and a low dissipation factor for the dielectric substrate 102, while the L-glass fabric enables the coefficient of thermal expansion (CTE) in the xy plane of the dielectric substrate 102 to match the CTE of the conductive coating 104. An additive material 112 capable of absorbing ultraviolet (UV) light (e.g., light having a wavelength of 180 nm to 400 nm) is dispersed in the perfluoro copolymer matrix 110. The presence of the UV responsive additive material 112 enables the flexible laminate 100 to be drilled by UV laser, for example, to form circuit structures such as vias through the thickness of the flexible laminate 100 .
[0085] The flexible laminate 100 is a planar structure having a thickness along the z-axis of less than about 200 μm or less than about 100 μm, such as 20 μm to 200 μm, such as 30 μm to 90 μm or 30 μm to 60 μm. The thickness of the dielectric substrate 102 constitutes most of the thickness of the flexible laminate 100. For example, the dielectric substrate 102 has a thickness along the z-axis of less than about 200 μm or less than about 100 μm, such as 20 μm to 200 μm, such as 30 μm to 90 μm or 30 μm to 60 μm. Each conductive plating layer 104a, 104b has a thickness along the z-axis of less than about 72 μm, such as less than about 18 μm, such as 5 μm to 18 μm.
[0086] The dielectric substrate 102 of the flexible laminate 100 has a low dielectric constant, for example, a dielectric constant of less than about 2.7 at 10 GHz, for example, 2.1 to 2.7, for example, 2.1 to 2.4. In the temperature range of 0° C. to 100° C., the dielectric constant has a thermal coefficient with a value of -250 ppm / ° C. to 50 ppm / ° C., for example, -100 ppm / ° C. to 50 ppm / ° C. or -50 ppm / ° C. to 25 ppm / ° C. The dielectric substrate 102 also has a low dissipation factor, for example, a dissipation factor of less than 0.0015 at 10 GHz, such as less than 0.001 or less than 0.0008, for example, 0.0002 to 0.001, for example, 0.0006 to 0.001, for example, 0.0006 to 0.0008.
[0087] The improved electrical properties (e.g., low dielectric constant and low dissipation factor) of the flexible laminate 100 enable designers to achieve improvements in insertion loss, for example, up to 25% or more for a given characteristic impedance relative to existing flexible materials. It is believed that low levels of ferromagnetic elements (e.g., Fe, Ni, or Co) in the conductive plating 104 (e.g., in the copper foil) can help achieve low insertion loss.
[0088] The coefficient of thermal expansion (CTE) of the dielectric substrate 102 and the CTE of the conductive coating 104 are similar in the xy plane of the flexible laminate 100. For example, when the conductive coating 104 is a copper foil, the CTE in the xy plane of the dielectric substrate 102 can be 5 ppm / °C to 25 ppm / °C, such as 16 ppm / °C to 22 ppm / °C, such as 14 ppm / °C to 20 ppm / °C. The matching of the CTE values between the dielectric substrate 102 and the conductive coating 104 provides the flexible laminate 100 with dimensional stability, such as dimensional stability of less than about 0.1%, such that the flexible laminate maintains its original dimensions within about 0.1% when subjected to removal of the conductive coating and temperature changes.
[0089] The conductive coating 104 of the flexible laminate 100 is firmly adhered to the dielectric substrate. For example, the peel strength between the dielectric substrate 102 and the conductive coating 104 is greater than 2 pounds per inch, such as greater than 4 pounds per inch, such as 2 pounds per inch to 20 pounds per inch or 4 pounds per inch to 20 pounds per inch. The flexible laminate 100 is mechanically robust to bending and can be bent within a range of bending radii typically found in electronic devices without causing any component of the flexible laminate 100 to fail. This flexibility facilitates the installation of the flexible laminate 100 into a device.
[0090] The flexible laminate 100 can be drilled by UV laser and is compatible with metallization techniques (e.g., plasma metallization) so that through-holes can be formed through the thickness of the flexible laminate 100 (e.g., along the z-axis of the flexible laminate 100). The dielectric substrate 102 of the flexible laminate 100 has a solder float resistance at 288° C. of at least 5 seconds, at least 10 seconds, at least 30 seconds, or at least 60 seconds, such as 5 seconds to 20 seconds, 10 seconds to 15 seconds, 10 seconds to 30 seconds, 10 seconds to 60 seconds, or 30 seconds to 60 seconds.
[0091] Flexible laminate 100 can be used for printed wiring boards, such as for flexible printed circuit board antennas. For example, the size and electrical properties of flexible laminate 100 can make flexible laminate 100 suitable for high-frequency applications, such as antennas for mobile devices that can be used on 5G communication networks, as discussed further below, or for use with automotive radar or other high-frequency applications. In some examples, multiple flexible laminates 100 themselves can be laminated into a multi-layer circuit board structure. The flexible laminate is substantially void-free and resists the formation of conductive anode filaments, which contributes to the electrical reliability of the flexible laminate as a printed wiring board substrate.
[0092] The low dielectric constant and low dissipation factor of the dielectric substrate 102 of the flexible laminate 100 are at least partially attributed to the composition of the perfluoro copolymer matrix 110. The perfluoro copolymer matrix 110 includes a fluorinated perfluoro copolymer, such as a fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer; a non-fluorinated perfluoro copolymer, such as a non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer. The fluorinated perfluoro copolymer, the non-fluorinated perfluoro copolymer, or both can be linear, non-branched polymers. The fluorinated perfluoro copolymer has low or zero polarity and therefore has a low dielectric constant and a low dissipation factor. However, the fluorinated perfluoro copolymer is generally non-reactive, for example, the fluorinated copolymer has poor adhesion to the L-glass fabric 108 and the conductive coating 104. The non-fluorinated perfluoro copolymer has reactive end groups (e.g., carboxyl or amide end groups) that are attracted to the L-glass fabric 108 and the conductive coating 104. The presence of these reactive end groups promotes adhesion between the perfluorocopolymer matrix and the L-glass fabric 108 and the conductive plating 104 .
[0093] In some examples, the perfluorocopolymer is prepared by aqueous dispersion polymerization, and after polymerization, every 10 6 The carbon atoms may contain at least about 400 reactive end groups. Most of these end groups are thermally unstable in the sense that when exposed to heat (such as heat encountered during extrusion and film formation) or film lamination conditions, they may undergo chemical reactions (such as decomposition and decarboxylation), discoloring the extruded polymer or filling the polymer with uneven bubbles, or both. In order to prepare the fluorinated perfluoro copolymers described herein, the polymerized perfluoro copolymer is stabilized to replace substantially all of the reactive end groups with thermally stable -CF3 end groups. An exemplary method of stabilization is to expose the fluoropolymer to a fluorinating agent (such as elemental fluorine), for example by methods disclosed in U.S. Pat. No. 4,742,122 and U.S. Pat. No. 4,743,658, the contents of which are incorporated herein by reference in their entirety.
[0094] Non-fluorinated perfluoro copolymers generally have higher dissipation factors than fluorinated perfluoro copolymers. The composition of the perfluoro copolymer matrix 110 can be adjusted to achieve a sufficiently low dielectric constant and a low dissipation factor for the dielectric substrate 102 and sufficient adhesion to the L-glass fabric 108 and the conductive coating 104. For example, the composition of the perfluoro copolymer matrix 110 can be adjusted to provide as much fluorinated copolymer as possible while still maintaining sufficient adhesion to the L-glass fabric 108 and the conductive coating 104. A sufficiently low dielectric constant for the dielectric substrate 102 is a dielectric constant of less than about 2.7 at 10 GHz, such as 2.1 to 2.7, such as 2.1 to 2.4. A sufficiently low dissipation factor for the dielectric substrate 102 is a dissipation factor of less than 0.0015 at 10 GHz, such as 0.0002 to 0.001, such as 0.0006 to 0.001, such as 0.0006 to 0.0008. In some examples, the adequacy of adhesion between the perfluoro copolymer matrix 110 and the L-glass fabric 108 and the conductive coating 104 is determined by the peel strength between the dielectric substrate 102 and the conductive coating 104. For example, if the peel strength is greater than 2 lbs / inch, such as greater than 4 lbs / inch, such as 2 lbs / inch to 20 lbs / inch or 4 lbs / inch to 20 lbs / inch, then the adhesion is sufficient. In some examples, the adequacy of adhesion between the perfluoro copolymer matrix 110 and the L-glass fabric 108 and the conductive coating 104 is determined by the propensity of the flexible laminate 100 to resist the formation of conductive anodic filaments (CAF), which will be discussed further below.
[0095] In some examples, the composition of the perfluoro copolymer matrix 110 is indicated by the ratio (e.g., weight ratio or volume ratio) of the fluorinated perfluoro copolymer to the non-fluorinated perfluoro copolymer. The weight percentage of the fluorinated perfluoro copolymer can be 50% to 90%, such as 50% to 80%, for example 50%, 60%, 70%, 75%, 80% or 90%; the weight percentage of the non-fluorinated perfluoro copolymer can be 10% to 50%, for example 10%, 20%, 25%, 30%, 40% or 50%.
[0096] In some examples, the composition of the perfluorocopolymer matrix 110 is indicated by the number (e.g., number concentration) of carboxyl end groups present in the perfluorocopolymer matrix 110. Non-limiting examples of such carboxyl end groups include -COF, -CONH 2 , -CO 2 CH 3 and -CO 2H, and is determined by polymerization aspects such as the selection of polymerization medium, initiator, chain transfer agent (if any), and buffer (if any). The number of carboxyl end groups per million carbon atoms present in the perfluorocopolymer matrix 100 can be 30 to 70, for example 35 to 65. The number of carboxyl end groups can be selected to achieve sufficient adhesion between the perfluorocopolymer matrix 110 and the L-glass fabric 108 and the conductive plating 104, while also achieving a sufficiently low dielectric constant and dissipation factor. For example, the number of carboxyl end groups can be selected so that CAF is not formed in the flexible laminate 100. In some examples, the composition of the fluorinated perfluorocopolymer and the non-fluorinated perfluorocopolymer is indicated by the number (e.g., number concentration) of carboxyl end groups present in each type of perfluorocopolymer. The fluorinated perfluorocopolymer can have less than 10 carboxyl end groups per million carbon atoms, for example 5 or less, or 1 or less, or less than 1 carboxyl end group. The non-fluorinated perfluoro copolymer may have 100 to 300 carboxyl end groups per million carbon atoms, for example 120 to 280 or 150 to 250 carboxyl end groups per million carbon atoms. The analysis and quantification of the carboxyl end groups in the perfluoro copolymer can be carried out by infrared spectroscopy, such as described in U.S. Patents 3,085,083, 4,742,122 and 4,743,658, all of which are incorporated herein by reference in their entirety. The presence of the thermally stable end group -CF3 (fluorinated product) is inferred from the absence of unstable end groups after fluorine treatment. Compared with other end groups, the presence of the -CF3 end group results in a reduced dissipation factor of the perfluoro copolymer.
[0097] The melt flow rate (MFR) of the fluorinated perfluorocopolymer, the non-fluorinated perfluorocopolymer, or both may also affect the adhesion between the perfluorocopolymer matrix 110 and the L-glass fabric 108 and the conductive plating 104. Polymers with a high MFR flow more easily during lamination of the flexible laminate 100 than polymers with a lower MFR. The flow of the perfluorocopolymer matrix 110 during the lamination process (discussed in more detail below) enables the perfluorocopolymer matrix 110 to fully encapsulate the fibers of the L-glass fabric 108, thereby producing a dielectric substrate 102 that is substantially free of voids (e.g., free of pores). The void-free dielectric substrate 102 resists CAF formation. For example, the MFR of the fluorinated perfluoro copolymer can be from 1 g / 10 min to 40 g / 10 min, such as from 2 g / 10 min to 15 g / 10 min, such as 2 g / 10 min, 4 g / 10 min, 6 g / 10 min, 8 g / 10 min, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 16 g / 10 min, 18 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min or 40 g / 10 min. The MFR of the non-fluorinated perfluoro copolymer can be from 1 g / 10 min to 40 g / 10 min, such as from 2 g / 10 min to 20 g / 10 min, such as 2 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min or 20 g / 10 min. The fluorinated and non-fluorinated perfluorocopolymers may be provided in a ratio resulting in a total MFR of the perfluorocopolymer matrix of 10 g / 10 min to 30 g / 10 min, e.g., 10 g / 10 min, 15 g / 10 min, 18 g / 10 min, 21 g / 10 min, 24 g / 10 min, 27 g / 10 min, or 30 g / 10 min.
[0098] Suitable materials for fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) perfluoro copolymers include Teflon® having an MFR of about 40 g / 10 min. TM Perfluoroalkane (PFA) 416HP or Teflon having an MFR of about 16 g / 10 min or 14 g / 10 min, respectively TM PFA 440HP (A / B) (The Chemours Company, Wilmington, DE). Suitable materials for non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) include Teflon® with an MFR of about 40 g / 10 min. TM PFA 316 or Teflon with an MFR of about 14 g / 10 min TM PFA 340 (Chemours).
[0099] The fluorinated perfluoro copolymer, the non-fluorinated perfluoro copolymer, or both have a high melting point, such as 250° C. to 350° C., for example 280° C. to 320° C., 290° C. to 310° C., for example about 305° C. The high melting point of the fluorinated perfluoro copolymer, the non-fluorinated perfluoro copolymer, or both results in the perfluoro copolymer matrix 100 being resistant to high temperatures and providing the dielectric substrate 102 with sufficient solder float resistance, such as at least 5 seconds, at least 10 seconds, at least 30 seconds, or at least 60 seconds, for example 5 seconds to 20 seconds, 10 to 15 seconds, 10 seconds to 30 seconds, 10 seconds to 60 seconds, or 30 seconds to 60 seconds at 288° C. as measured according to the IPC-TM-650 test method.
[0100] The composition of the perfluorocopolymer matrix 110 may be selected to render the dielectric substrate 102 compatible with plasma processing, for example, for metallization of vias formed through the thickness of the flexible laminate 100 .
[0101] Specific examples of fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers suitable for inclusion in the perfluorocopolymer matrix 100 include Teflon® having an MFR of about 40 g / 10 min. TM Perfluoroalkane (PFA) 416HP or Teflon with MFR of about 14 g / 10 min TM PFA 440HP (The Chemours Company, Wilmington, DE). Specific examples of non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers suitable for inclusion in the perfluorocopolymer matrix 100 include Teflon® having an MFR of about 40 g / 10 min. TM PFA 316 or Teflon with MFR of about 14 g / 10 min TM PFA 340 (The Chemours Company).
[0102] In some examples, the perfluorocopolymer matrix 100 is formed of a single type of perfluorocopolymer having both fluorinated end groups and reactive end groups (e.g., rather than a mixture of fluorinated perfluorocopolymers and non-fluorinated perfluorocopolymers). The ratio of fluorinated end groups to reactive end groups in the single type of perfluorocopolymer is selected to achieve adequate adhesion between the perfluorocopolymer matrix 110 and the L-glass fabric 108 and a sufficiently low dielectric constant and dissipation factor.
[0103] The presence of the woven L-glass fabric 108 enables the CTE of the dielectric substrate 102 to be matched to the CTE of the metal foil 104. The woven L-glass fabric 108 embedded in the perfluorocopolymer matrix 110 is formed from strands of polarized glass (eg, L-glass).
[0104] The composition of L-glass is shown in Table 1. The composition of E-glass is also shown for comparison. L-glass has a lower CTE than the perfluoro copolymer matrix 110, such as 2.5 ppm / °C to 4 ppm / °C, for example, 2.5 ppm / °C to 3 ppm / °C or 3 ppm / °C to 4 ppm / °C. By adjusting the ratio of the perfluoro copolymer matrix 110 to the woven glass fabric 108, the CTE of the dielectric substrate 102 in the xy plane can be matched to the in-plane CTE of the metal foil 104, thereby providing dimensional stability to the flexible laminate 100. For example, the dielectric substrate 102 can include 5 volume percent to 20 volume percent of the woven L-glass fabric 108 and 80 volume percent to 95 volume percent of the perfluoro copolymer matrix 110 and the woven glass fabric 108. The CTE in the xy plane of the dielectric substrate 102 may be 5 ppm / °C to 25 ppm / °C, such as 16 ppm / °C to 22 ppm / °C, such as 14 ppm / °C to 20 ppm / °C, thereby providing a dimensional stability of less than about 0.1%. In contrast, the CTE of the perfluorocopolymer matrix 110 alone may be 100 ppm / °C to 300 ppm / °C.
[0105] L-Glass E-Glass <![CDATA[SiO 2 ]]> 52-56% 52-56% CaO 0-10% 20-25% <![CDATA[Al 2 THE 3 ]]> 10-15% 12-16% <![CDATA[B 2 THE 3 ]]> 15-20% 5-10% MgO 0-5% 0-5% <![CDATA[Na 2 Okay, K 2 O]]> 0-1% 0-1% <![CDATA[TiO 2 ,LiO 2 ]]> 0-5% 0%
[0106] Table 1. Composition of L-glass
[0107] L-glass has a low dielectric constant, such as 4.0 to 5.0, for example 4.5 to 5.0 or 4.5 to 4.8 at 10 GHz. Thus, the dielectric substrate 102 has a low dielectric constant and low loss even in the presence of an L-glass fabric embedded in a perfluorocopolymer matrix. L-glass also has a low dissipation factor, such as 0.002 to 0.003, for example 0.002, 0.0023, 0.0025, 0.0028, or 0.003 at 10 GHz.
[0108] The woven L-glass fabric 108 has a thickness of less than about 100 μm, such as about 30 μm to 100 μm or 10 μm to 30 μm, thereby facilitating the realization of a thin dielectric substrate 102. The basis weight of the quartz fabric 108 is less than about 1000 g / m 2 , for example less than about 50 g / m 2 , for example 10g / m 2 Up to 50g / m 2 In one specific example, the L-glass fabric 108 is NL1035 NL-glass fabric (Asahi Kasei Corporation, Tokyo, Japan).
[0109] In some examples, the woven L-glass fabric 108 is subjected to one or more surface treatments to improve the wettability of the fibers of the woven L-glass fabric 108 by the perfluoro copolymer matrix 110, remove residual organic matter, or mechanically change the surface of the fibers to enhance the adhesion between the fibers of the L-glass fabric 108 and the perfluoro copolymer matrix 110. The purpose of the surface treatment can be to promote substantially complete wetting of the L-glass fibers by the perfluoro copolymer so that the perfluoro copolymer fully encapsulates the L-glass fiber (e.g., L-glass yarn) bundle. The sufficient encapsulation and adhesion of the perfluoro copolymer to the L-glass fiber bundle enables the dielectric substrate 102 to be substantially free of voids (e.g., pores), which in turn helps prevent the formation of conductive anode filaments and the occurrence of electromigration during post-processing (e.g., during the formation of vias through the thickness of the flexible laminate 100).
[0110] The surface treatment may include heat treatment to remove residual organic matter (e.g., residual starch) from the surface of the L-glass fiber, so that the clean L-glass surface is exposed to the perfluoro copolymer. The surface treatment may include adding an adhesion promoter such as methacrylate silane, aminosilane or fluorosilane to the surface of the L-glass fiber. The surface treatment may include plasma treatment or corona treatment. The surface treatment may include coating with a polymer coating (such as a fluoropolymer, for example, perfluoroalkane (PFA), fluorinated ethylene propylene (FEP) or Teflon TM The surface treatment of L-glass fabric 108 can be carried out by treating the L-glass fabric 108 with a fluorinated polymer (e.g., amorphous fluoropolymer) to form a polymer (e.g., fluoropolymer) film on the surface of the L-glass fiber. For example, the L-glass fabric can be immersed in a solution containing a fluorinated polymer dispersion to form a monolayer of a fluorinated polymer on the surface of the L-glass fiber. The surface treatment can include treating with fluorinated silane to form a fluorinated molecular layer, such as a monolayer, on the surface of the L-glass fiber. A combination of surface treatments can be applied, such as heat treatment, followed by plasma or corona treatment. The surface treatment applied to the L-glass fabric 108 can improve the wettability of the perfluoro copolymer matrix 110 to the fiber, so that the perfluoro copolymer matrix 110 can better encapsulate the fibers of the L-glass fabric 108, and make the adhesion between the perfluoro copolymer matrix 110 and the fibers of the L-glass fabric 108 stronger, thereby helping to form a void-free dielectric substrate 102 that resists CAF formation.
[0111] The wettability of L-glass fabric can be characterized by water contact angle (WCA). The surface treated woven L-glass fabric can have a WCA of 0° to 60°.
[0112] In some examples, the laminate structure can be designed to achieve good encapsulation of the L-glass fabric, for example, in addition to or in lieu of applying a surface treatment to the L-glass fabric. Figure 2, an exemplary metal-clad flexible laminate can be manufactured by laminating a set of layers 150. The set of layers includes a plurality of fluoropolymer films, including non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) layers 162a, 162b disposed on either side of the L-glass fabric 108, and perfluoro copolymer layers 164a, 164b containing fluorinated perfluoro copolymers and non-fluorinated perfluoro copolymers disposed on the outer sides facing each non-fluorinated layer 162. Conductive plating layers (such as the above-mentioned metal (e.g., copper) foils 104a, 104b) are disposed on both outer sides of the set of layers 150. When Figure 2 When the structure shown in is laminated to produce a flexible laminate (see further discussion of the lamination process below), the non-fluorinated layer 162 encapsulates the L-glass fabric 108 so that the non-fluorinated layer 162 and the perfluorocopolymer layer 164 form a matrix in which the L-glass fabric 108 is embedded, for example forming a dielectric substrate for the flexible laminate.
[0113] Reference again Figure 1 , an additive material 112 is dispersed (e.g., uniformly dispersed) in the perfluorocopolymer matrix 110. The additive material 112 is a material capable of absorbing UV light so that the flexible laminate 100 can be processed by a UV drilling process, for example, to form a via between the top surface and the bottom surface 106 of the flexible laminate 100. The additive material 112 is present in the dielectric substrate 102 at a volume percentage of less than 2%, such as 1 volume percent to 2 volume percent, such as 1 volume percent, 1.25 volume percent, 1.5 volume percent, or 2 volume percent. The additive material 112 can be a material having a relatively low dielectric constant (e.g., a dielectric constant of 10 to 1000) such that including the additive material 112 in the perfluorocopolymer matrix 110 does not significantly increase the dielectric constant or dissipation factor of the dielectric substrate 102. For example, including less than 2 volume percent of the additive material 112 can result in an increase in the dielectric constant of the dielectric substrate 102 of less than 10%, such as less than 5% or less than 2%.
[0114] In some examples, the additive material 112 is an inorganic particle, such as cerium oxide (CeO 2 ), titanium dioxide (TiO 2 ), silicon dioxide (SiO 2 ), barium titanate (BaTiO 3 ), calcium titanate (CaTiO 3), zinc oxide (ZnO), or other suitable material. The particles may have a diameter of less than about 5 μm, less than about 2 μm, less than about 1 μm, or less than about 0.5 μm, such as 0.1 μm to 0.5 μm. For example, smaller particles are generally more effective UV light absorbers than larger particles of similar composition. In some examples, additive material 112 is an organic (e.g., polymer) additive blended into perfluorocopolymer matrix 110, such as a low-loss thermosetting material such as polyimide. In some examples, both inorganic particles and organic additives are used as additive materials.
[0115] The copper foil 104 of the flexible laminate 100 provides a platform on which a conductive pattern can be defined, for example, so that the flexible laminate 100 can be used as a printed wiring board. In some examples, the copper foil 104 is disposed on the surface 106 of the dielectric substrate 102 by a mechanical process (e.g., a roll-to-roll lamination process). For example, the copper foil can be an electrodeposited copper foil or a rolled copper foil. In some examples, the copper foil 104 is deposited (e.g., electrolytically plated) onto the dielectric substrate 102.
[0116] The copper foil 104 has a thickness of less than about 72 μm, for example, less than about 18 μm, for example, 10 μm to 18 μm. The copper foil 104 has a low root mean square (RMS) roughness, such as less than 1 μm, for example, less than 0.5 μm RMS roughness measured by non-contact interferometry. The low RMS roughness of the copper foil 104 helps to maintain a low insertion loss of the circuit made of the flexible laminate 100. In some examples, the RMS roughness of the copper foil 104 is selected to balance the low insertion loss (e.g., which can be achieved by a low RMS roughness) with good adhesion between the copper foil 104 and the dielectric substrate 102 (e.g., which can be achieved by a higher RMS roughness). For example, as discussed above, a sufficiently high peel strength between the dielectric substrate 102 and the copper foil 104 is greater than 2 pounds / inch, for example, greater than 4 pounds / inch, for example, 2 pounds / inch to 20 pounds / inch or 4 pounds / inch to 20 pounds / inch. Peel strength.
[0117] The copper foil 104 has a purity of at least about 99.9%. The surface chemistry of the copper foil 104 can be affected by surface treatments, such as treatment with zinc, treatment with thermal stability additives, and anti-oxidation treatments. These surface treatments can be applied to one or both surfaces of the copper foil 104. Elements such as iron and zinc have been found to be effective in increasing peel strength without significantly degrading the electrical properties of the substrate.
[0118] As discussed above, the dielectric substrate 102 of the flexible laminate 100 is substantially void-free and has sufficient adhesion between the perfluoro copolymer matrix 110 and the L-glass fabric 108, which enables the flexible laminate to resist the formation of conductive anodic filaments (CAF). CAF is a metal filament formed in a void or weak area of a dielectric substrate, such as due to metal electromigration caused by, for example, an applied electric field. For example, when CAF creates a short-circuit channel between vias passing through a printed wiring board, the formation of CAF may cause electrical failure. When the resistance drops less than ten times during the entire test duration, that is, when the resistance is greater than 10 megohms after the initial 96-hour equilibrium period, it can be considered that the flexible laminate has not formed CAF. For example, according to the application standard, the CAF test can last for up to 1000 hours or more, and the applied voltage is 100VDC to 1000VDC.
[0119] Figure 3A An example of CAF formation is shown in . Figure 3A A hypothetical laminate 200 is shown having a dielectric matrix 202 with glass fibers 204 embedded therein. Through holes (sometimes also referred to as vias) 206 are formed through the thickness of the laminate 200 and are plated with a metal 208, such as copper. Application of an electric field causes the metal 208 to anodic dissolve, migrate, and redeposit in the dielectric matrix 202, such as at the interface between the dielectric matrix 202 and the glass fibers 204, thereby forming filaments 210 extending between adjacent vias 206.
[0120] Figure 3B Another example of CAF formation is shown in a hypothetical laminate 250 having a dielectric matrix 252 in which glass fibers 254 are embedded and conductor patterns 262 (e.g., copper patterns) defined on the top, bottom, and interior surfaces of the laminate 250. Metal (e.g., copper) wires 260 are formed at the interface between the conductor pattern 262 and the glass fibers 254.
[0121] See again Figure 1 , the dielectric substrate 102 of the flexible laminate is substantially void-free and has strong adhesion between the perfluoro copolymer matrix 110 and the L-glass fabric 108. This is achieved, for example, by the properties of the perfluoro copolymer (e.g., the number concentration of reactive end groups), the surface chemistry of the L-glass fabric, and manufacturing parameters such as pressure and temperature (discussed below). In addition, the arrangement of the L-glass fabric 108 in the perfluoro copolymer matrix 110 is such that there is substantially no contact between the fibers of the fabric and the conductive plating 104. Therefore, CAF formation in the dielectric substrate 102 is minimized, and the flexible laminate 100 can be used as a reliable and robust printed wiring board substrate.
[0122] refer to Figure 4The multilayer printed wiring board 300 may be formed by a plurality of the above-mentioned flexible laminates 100. Figure 4 In the example of , the multilayer printed wiring board 300 includes two flexible laminates 100a, 100b connected by an adhesive layer 302. Vias (also called through-holes; not shown) that pass through all or part of the thickness of the multilayer printed wiring board can be defined, for example, by UV drilling, where the UV energy is absorbed by the additive material in the dielectric substrate of the flexible laminate 100. The vias can be plated with a metal, such as a copper film. The adhesive layer 302 can be, for example, an adhesive that can be bonded at a temperature below the melting point of the perfluorocopolymer matrix of the flexible laminate 100. In some examples, the adhesive is a thermoplastic adhesive that can be bonded at a temperature of 0°C to 50°C below the melting point of the perfluorocopolymer matrix. In some examples, the adhesive is a thermosetting adhesive that can be bonded at a temperature of 0°C to 200°C below the melting point of the perfluorocopolymer matrix, for example at a temperature of 150°C to 250°C.
[0123] refer to Figure 5 , multiple (here three) flexible laminates 100 are laminated together to form a multilayer printed wiring board 400. The central flexible laminate 100c includes a top conductive plating layer and a bottom conductive plating layer. The flexible laminates 100d and 100e each include a single conductive plating layer. The flexible laminates 100c and 100d are bonded to the central flexible laminate 100e by adhesive layers 402a and 402b, respectively. The adhesive layers 402a and 402b can be, for example, an adhesive that can be bonded at a temperature lower than the melting point of the perfluorocopolymer matrix of the flexible laminate 100. In some examples, the adhesive is a thermoplastic adhesive that can be bonded at a temperature lower than the melting point of the perfluorocopolymer matrix of 0°C to 50°C. In some examples, the adhesive is a thermosetting adhesive that can be bonded at a temperature lower than the melting point of the perfluorocopolymer matrix of 0°C to 200°C.
[0124] Vias (not shown) may be defined through all or a portion of the thickness of the multilayer printed wiring board 400, for example, by UV drilling.
[0125] The printed wiring board made from the flexible laminate 100 described herein can be used in various applications, such as high frequency applications, such as high frequency communication applications. Figure 6, a printed wiring board 502 including one or more flexible laminates may be used for an antenna or antenna feeder of a communication device 500 (e.g., a mobile communication device) that may be operated on a 5G communication network. For example, a flexible laminate may be used as a substrate for a printed wiring board of a communication device antenna or antenna feeder to connect electronic components of a device located on different planes. A printed wiring board 504 including one or more flexible laminates may be used in communication network equipment, such as in a transmission antenna used in a tower 508 of a cellular communication network. Printed wiring boards including flexible laminates may also be used in other applications, such as in a camera feeder used in a mobile computing device.
[0126] The flexible laminate described herein can be manufactured by a lamination process. Figure 7 In one example, the L-glass fabric 108 is disposed between two perfluoro copolymer films 120a, 120b. Each perfluoro copolymer film 120a, 120b has a thickness of 10 μm to 100 μm, for example, 10 μm to 80 μm, 10 μm to 60 μm, or 20 μm to 50 μm. The conductive plating layers 104a, 104b are disposed on the perfluoro copolymer films 120a, 120b, respectively. For example, the conductive plating layer 104 is an electrodeposited copper foil or a rolled annealed copper foil. Each conductive plating layer 104a, 104b has a thickness of less than about 72 μm, for example, less than about 18 μm, for example, 10 μm to 18 μm.
[0127] The material layers 104, 108, 120 are heated and compressed to consolidate the material layers, thereby forming the flexible laminate 100. In some examples, in a second processing step, the L-glass fabric 108 and two perfluorocopolymer films 120a, 120b are laminated to form a dielectric substrate, and a conductive plating layer (e.g., copper foil) is electrodeposited onto the dielectric substrate.
[0128] The parameters of the lamination process (e.g., temperature, time, and pressure) are selected to achieve a target viscosity of the perfluoro copolymer that enables the perfluoro copolymer to flow, thereby wetting and encapsulating the glass strands of the L-glass fabric 108 and enabling good adhesion between the perfluoro copolymer and the conductive coating 104. For example, the process parameters are selected so that the perfluoro copolymer reaches a zero shear viscosity of 2000 Pa-s to 5000 Pa-s at 330° C. The temperature may be higher than the melting point of the perfluoro copolymer, such as 10° C. to 30° C. higher than the melting point of the perfluoro copolymer. For example, the temperature may be 300° C. to 400° C., such as 320° C. to 330° C., such as 300° C., 320° C., 340° C., 360° C., 380° C., or 400° C. The heating rate may be 1° C. / min. to 5° C. / min., such as 1° C. / min., 2° C. / min., 3° C. / min., 4° C. / min., or 1° C. / min. The pressure applied to the material layer can be 100 psi to 1000 psi, such as 200 psi to 1000 psi or 600 psi to 1000 psi. The dwell time (e.g., for a static lamination process) can be 30 minutes to 120 minutes, such as 30 minutes, 60 minutes, 90 minutes or 120 minutes.
[0129] Figure 7 An isobaric roll-to-roll lamination process using a set of rollers 600 is depicted. In some examples, the roll-to-roll lamination process is an isochoric, gap-controlled lamination process. In some examples, the lamination process is a static lamination process in which material layers are pressed between heated platens.
[0130] The perfluoro copolymer film 120 is formed by, for example, melt processing and extrusion. In some examples, the additive material is mixed into the molten fluorinated perfluoro copolymer, and the mixture of the fluorinated copolymer and the additive material is mixed with the molten non-fluorinated perfluoro copolymer. In some examples, the additive material is mixed into the molten non-fluorinated perfluoro copolymer, and the mixture of the non-fluorinated perfluoro copolymer and the additive material is mixed with the molten fluorinated perfluoro copolymer. The resulting perfluoro copolymer mixture is extruded to form a perfluoro copolymer film. Mixing the additive material with the non-fluorinated perfluoro copolymer helps to integrate and disperse the additive material throughout the perfluoro copolymer film.
[0131] Figure 8is a flow chart of an exemplary process for making flexible laminate 100. An additive material capable of absorbing ultraviolet light is dispersed in a non-fluorinated perfluoro copolymer, such as a non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) perfluoro copolymer (700). The additive material is, for example, particles of cerium oxide, titanium dioxide, silicon dioxide, barium titanate, calcium titanate, or zinc oxide; or a polymer additive, such as a polyimide. The non-fluorinated perfluoro copolymer with the dispersed additive material is mixed (702) with a fluorinated perfluoro copolymer, such as a fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) perfluoro copolymer, to form a perfluoro copolymer mixture. The perfluoro copolymer mixture is melt processed and extruded to form a perfluoro copolymer film (704).
[0132] The woven L-glass fabric is exposed to a surface treatment, such as heat treatment, corona or plasma treatment, or a coating is formed on the surface of the fibers of the L-glass fabric (706). The copper foil, such as an electrodeposited copper foil or a rolled annealed copper foil, is also exposed to a surface treatment, such as heat treatment, corona or plasma treatment, or deposition of an adhesion promoter or thermal stability additive (708).
[0133] A layered stack of materials (710) is formed, the layered stack comprising a treated L-glass fabric disposed between two perfluorocopolymer films, with treated conductive plating on both the top and bottom of the stack. The layered stack of materials is laminated by applying heat and pressure, for example, in a static lamination process or a roll-to-roll lamination process to form a flexible laminate (712).
[0134] Example
[0135] The following polymers and polymer dispersions were used in the examples.
[0136] PFA1: Teflon TM PFA 440HP(A / B) (Chemours), a high purity fluorinated perfluoroalkoxy (PFA) melt processible resin, having an MFR of 16 g / 10 min (for "A") and 14 g / 10 min (for "B").
[0137] PFA2: Teflon TM PFA 340 (Chemours), a general purpose non-fluorinated PFA melt processible resin, has an MFR of 14 g / 10 min.
[0138] PFA3: Teflon TM PFA 416HP (Chemours), a high purity fluorinated PFA melt processable resin, has an MFR of 40 g / 10 min.
[0139] Example 1: Mechanical Characterization of Flexible Copper Clad Laminates Containing L-Glass or Quartz Fabric
[0140] Experiments were conducted to study the thickness, flatness and dimensional stability of copper-clad laminates incorporating L-glass fabrics and quartz fabrics. PFA films were combined with NL1035 NL-glass fabrics from Asahi or 1027C-04 quartz fabrics from Shin-Etsu and 12 μm thick BHFX-P92F-HG rolled copper foils from JX Nippon Mining & Metals Corporation (Tokyo, Japan) to form flexible copper-clad laminates. PFA films consisted of 50 wt % PFA1, 25 wt % PFA2 and 22.5 wt % PFA3 and 2.5 wt % TiO2 particles (50.63 vol % PFA1, 25.31 vol % PFA2 and 22.78 vol % PFA3 and 1.28 vol % TiO2 particles), and were treated with corona treatment on both sides of the film. The materials were laminated in a hot oil vacuum press at a peak temperature of 320°C and a pressure of 200 psi.
[0141] Details of the experimental configuration including the materials used are shown in Table 2. The five values in the "Configuration" column refer to the thickness of the copper plating on each side of the laminate (12 μm in this example), the thickness of the perfluorocopolymer film used to make the laminate (54 μm in this example), and the fabric type (NL1035 L-glass or 1035 quartz glass fabric in this example). The materials were laminated in a hot oil vacuum press at a dwell temperature of 320°C and a pressure of 200 psi with a dwell time of 60 minutes, a vacuum of 1 atm, and a ramp rate of 2°C / min. Prior to testing, the samples were equilibrated at 23°C and 50% relative humidity for 24 hours.
[0142]
[0143] Table 2. Experimental details .
[0144] Laminates are shown in Fig. 9 The flatness of each laminate is visually characterized in the photograph. Fig. 9 It can be seen that the laminate comprising the L-glass fabric is flatter than the laminate comprising the quartz fabric.
[0145] The thickness of each laminate was measured after etching according to IPC TM-650 2.2.18 test method and the results are shown in Fig.10 In general, L-glass laminates are thicker than quartz glass laminates. The thickness and estimated squeeze-out results are shown in Table 3. The estimated squeeze-out was measured by measuring the film flow distance from the edge of the laminate when squeezed. The resin content of each laminate is shown in Fig.11 middle.
[0146]
[0147]
[0148] Table 3. Experimental test data of the experiment are detailed in Table 2 .
[0149] The dimensional stability results of the laminates tested in the machine direction (MD) and cross direction (CMD) are shown in Fig. 12A (according to IPC TM-650 2.2.4b to test) and Fig. 12B (Tested in accordance with IPC TM-6502.2.4c). These results show that the dimensional stability values of the L-glass laminates are lower than those of the quartz glass laminates.
[0150] Example 2: Characterization of Flexible Copper Clad Laminates Containing L-Glass or Quartz Fabric
[0151] Additional experiments were conducted to investigate the relationship between thickness and flatness and dimensional stability. Various types of PFA membranes were combined with various types of glass fabrics (including 1017C-02, 1027C-04, 1035C-04, 1078C-04 or 2116C-04 quartz fabrics from Shin-Etsu, or NL1027, NL1035, NL-1078 or L2-1078 L-glass fabrics or NL-glass fabrics from Asahi). PFA membranes and glass fabrics were laminated with 12 μm thick BHFX-P92F-HG rolled copper foil from JX Nippon Mining & Metals Corporation to form flexible copper-clad laminates. In some cases, R101 titanium dioxide particles (Chemours) were added at a filler loading of 1.25% by volume. The materials were laminated in a hot oil vacuum press at a peak temperature of 320°C and a pressure of 200 psi with a dwell time of 60 minutes, a vacuum of 1 atm, and a ramp rate of 2°C / min.
[0152] ●Test various PFA membranes, including the following:
[0153] PFA membrane 1, composed of 50 wt% PFA1, 25 wt% PFA2 and 22.5 wt% PFA3 and 2.5 wt% TiO 2 Particles (50.63 vol% PFA1, 25.31 vol% PFA2 and 22.78 vol% PFA3 and 1.28 vol% TiO 2 particles) and treated with corona treatment on both sides of the film.
[0154] PFA membrane 2, composed of 75 wt% PFA3 and 25 wt% PFA 2, with 2.5 wt% (1.25 vol%) R101 TiO 2 Granule mixing.
[0155]
[0156]
[0157] Table 4. Experimental details .
[0158] The data obtained from these experiments are shown in Figure 13-Figure 17 middle. Fig.13 is a graph of a visual representation of the flatness of each laminate, with a rating of 1 being lowest (worst flatness) and 5 being best (very flat). Fig.14 is a graph of the thickness of each laminate measured after etching according to the IPC TM-650 2.2.18 test method. These results show that, in general, thicker laminates are flatter than thinner laminates. Fig.15 is a graph of the resin content of each laminate.
[0159] The dielectric constant and dissipation factor of each sample were also measured. The dielectric constant and dissipation factor were measured according to the IPC TM-650 2.5.5.13 test method at 23°C and 50% relative humidity. The results are shown in Fig.16 and Fig.17 The dimensional stability results according to Method B and Method C are shown in Fig.18A and Fig.18B middle.
[0160] These results show the effect of L-glass fabric versus quartz glass fabric on the dielectric constant and dissipation factor of the laminate for the same resin content.
[0161] Example 3: Effect of end group content on copper clad laminate
[0162] The effect of end group content on the properties of copper-clad laminates was evaluated by preparing PFA1 (fluorinated PFA) and PFA2 (non-fluorinated PFA) resins in combination with R101 titanium dioxide (Chemours) in various ratios of PFA2 to PFA1. A mixture of about 70 grams of resin was dry-mixed and then fed into a Rheometer Services Inc. System 10 intermittent mixer equipped with a 60cc volume mixing bowl containing a roller blade. These blends were mixed at 350°C for 10 minutes at 150rpm to disperse all components. The mixture was then taken out of the bowl and subsequently pressed into a plate having a thickness of about 100mm×100mm×about 0.20mm at 350°C for electrical testing and subsequent lamination. The pressed film was tested and found to have the electrical properties shown in Table 5:
[0163]
[0164]
[0165] Table 5. Electrical properties of molded PFA films with different PFA2 to PFA1 ratios at 10 GHz .
[0166] As expected, the dielectric constant (Dk) remains fairly consistent with PFA2 loading, and the dissipation factor (DF) increases in a linear manner with increasing PFA2 concentration in the blend.
[0167] Measurements were also performed to determine the selected blends per 10 6 The total number of carboxyl terminal groups of carbon atoms was calculated, and the results are shown in Table 6.
[0168] Load PFA2 weight% PFA1 wt% TiO2 weight% Carboxyl terminal group 100% PFA2 97.50% 0.00% 2.50% 214 Polymer Basics 100% 0% 75% PFA2 73.13% 24.38% 2.50% 178 Polymer Basics 75% 25% 50% PFA2 48.75% 48.75% 2.50% 95 Polymer Basics 50% 50% 25% PFA2 24.38% 73.13% 2.50% 53 Polymer Basics 25% 75% 0% PFA2 0.00% 97.50% 2.50% 7 Polymer Basics 0% 100%
[0169] Table 6. End Group Levels of PFA Blends with Different 340 and 440 Ratios
[0170] As with the dissipation factor data, it was found that the addition of PFA2 to the blend increased the amount of end groups measured in a generally linear manner. A graph showing the measured dissipation factor as a function of end group level is shown in Fig.19 This serves to show how the level of end groups has a direct impact on the measured electrical properties of the blend films.
[0171] These blended PFA films were combined with NL2116 fabric (Asahi Kasei, Japan) and 35 μm EXP-WS copper foil (Furukawa Electric Co., Ltd, Japan) and laminated in an electric hot press (PHI, USA) at 320° C. and 400 psi for 60 minutes dwell time to form copper clad laminates.
[0172] Experimental details are shown in Table 7A and Table 7B.
[0173] Run ID structure PFA membrane Membrane MFR Number of end groups G2-134-1 12 / 233 / 2116 / 224 / 12 100% PFA2 14.0 214.0 G2-134-2 12 / 216 / 2116 / 244 / 12 75% PFA2 / 25% PFA1 14.0 178.3 G2-134-3 12 / 222 / 2116 / 220 / 12 50% PFA2 / 50% PFA1 14.0 95.0 G2-134-4 12 / 215 / 2116 / 220 / 12 25% PFA2 / 75% PFA1 14.0 52.6 G2-134-5 12 / 240 / 2116 / 213 / 12 15% PFA2 / 85% PFA1 14.0 33.6 G2-134-6 12 / 207 / 2116 / 216 / 12 10% PFA2 / 90% PFA1 14.0 22.8 G2-134-7 12 / 219 / 2116 / 213 / 12 5% PFA2 / 95% PFA1 14.0 12.0 G2-134-8 12 / 214 / 2116 / 210 / 12 100% PFA1 14.0 6.6
[0174] Table 7A. Experimental details.
[0175]
[0176] Table 7B. Experimental details .
[0177] The laminates were tested for various properties. The results are shown in Table 8A and Table 8B.
[0178]
[0179] Table 8A. Experimental test results of PFA2 / PFA1 mixing study .
[0180]
[0181] Table 8B. Experimental test results of PFA2 / PFA1 mixing study .
[0182] Discover every 10 6 There is a very good correlation between the total number of end groups of carbon atoms and the dissipation factor, and a suggested relationship between copper peel strength and end groups. These data can be found in Fig. 20 and Fig.21 middle.
[0183] Example 4: Sharpie Wicking Behavior of Commercially Available Laminates
[0184] In the Sharpie wicking test, a hole is made in the flexible laminate and the Sharpie is rubbed around the edges of the hole. A permanent marker was used and the hole was cleaned with isopropyl alcohol to remove excess ink. The radial distance from the edge of the hole into which the ink was wicked was measured. Without being bound by theory, it is believed that this wicking test serves as an indicator of the adhesion between the fibers of the quartz fabric and the perfluorocopolymer matrix; poor adhesion or poor encapsulation will leave voids into which the ink can be wicked, resulting in a longer travel distance. Conversely, a substrate with good adhesion and good encapsulation will exhibit a low wicking distance.
[0185] The Sharpie wicking test results of the laminate can predict the performance of the laminate under the CAF test. To demonstrate this correlation, commercially available materials known to have good CAF resistance were subjected to sharpie wicking tests. The results of these tests are shown in Table 9. These results show that sharpie wicking results of less than 0.5 mm correspond to materials with good CAF resistance. It is believed that flexible copper clad laminates containing L-glass exhibit sharpie wicking of less than 1 mm.
[0186]
[0187]
[0188] Table 9. Sharpie wicking results for commercially available materials .
[0189] Specific embodiments of the subject matter have been described. Other embodiments are within the scope of the following claims. For example, the actions recited in the claims can be performed in a different order and still achieve the desired results. As an example, the processes depicted in the accompanying drawings do not necessarily require the particular order or sequential order shown to achieve the desired results. In some specific implementations, multitasking and parallel processing may be advantageous.
Claims
1. A laminated product, comprising: A dielectric substrate, the dielectric substrate comprising: a perfluorocopolymer matrix comprising a fluorinated perfluorocopolymer and a non-fluorinated perfluorocopolymer; L-glass fabric, said L-glass fabric being embedded in said perfluorocopolymer matrix; and an additive material dispersed in the perfluorocopolymer matrix, wherein the additive material is capable of absorbing ultraviolet light; and A conductive plating layer is disposed on a surface of the dielectric substrate.
2. The laminate according to claim 1, wherein the L-glass fabric comprises yarns of L-glass, NL-glass or L2-glass. 3 . The laminate according to claim 1 , wherein the laminate has a thickness of 20 μm to 200 μm. 4 . The laminate according to claim 3 , wherein the laminate has a thickness of 30 μm to 90 μm. 5 . The laminate according to claim 4 , wherein the laminate has a thickness of 30 μm to 60 μm.
6. A laminate according to any one of the preceding claims, wherein the dielectric substrate has a dielectric constant of 2.10 to 2.70 at 10 GHz.
7. The laminate according to claim 6, wherein the dielectric constant of the dielectric substrate is 2.10 to 2.
40.
8. The laminate according to any one of the preceding claims, wherein the dielectric substrate has a thermal coefficient of dielectric constant with a value of -250 ppm / °C to +50 ppm / °C in the temperature range of 0°C to 100°C.
9. The laminate according to any one of the preceding claims, wherein the dielectric substrate has a dissipation factor of less than 0.0015 at 10 GHz.
10. The laminate of claim 9, wherein the dielectric substrate has a dissipation factor of 0.0006 to 0.001 at 10 GHz.
11. The laminate of claim 10, wherein the dielectric substrate has a dissipation factor of 0.0006 to 0.0008 at 10 GHz.
12. The laminate according to any one of the preceding claims, wherein the laminate has a planar shape defining an XY plane, and wherein the laminate has a coefficient of thermal expansion in the XY plane of 5 ppm / °C to 25 ppm / °C. 13 . The laminate according to claim 12 , wherein the coefficient of thermal expansion of the laminate in the XY plane is 14 ppm / ° C. to 20 ppm / ° C.
14. The laminate according to claim 12, wherein the laminate has a coefficient of thermal expansion in the XY plane of 16 ppm / °C to 22 ppm / °C.
15. The laminate according to any one of the preceding claims, wherein the fluorinated perfluoro copolymer comprises a fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer, and wherein the non-fluorinated perfluoro copolymer comprises a non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer.
16. The laminate according to any one of the preceding claims, wherein the perfluorocopolymer matrix comprises 50 to 90 weight percent of the fluorinated perfluorocopolymer.
17. The laminate of claim 16, wherein the perfluorocopolymer matrix comprises 10 to 50 weight percent of the non-fluorinated perfluorocopolymer.
18. The laminate of any one of the preceding claims, wherein the number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix is sufficient to prevent the laminate from forming conductive anodic filaments (CAFs).
19. The laminate of any one of the preceding claims, wherein the number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix provides the laminate with a peel strength between the dielectric substrate and the conductive coating greater than 2 pounds per inch.
20. The laminate according to any one of the preceding claims, wherein the number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix is from 30 to 70.
21. The laminate according to any one of the preceding claims, wherein the fluorinated perfluorocopolymer has 5 or fewer carboxyl end groups per million carbon atoms.
22. The laminate according to any one of the preceding claims, wherein the non-fluorinated perfluorocopolymer has from 100 to 300 carboxyl end groups per million carbon atoms.
23. The laminate according to any one of the preceding claims, wherein the perfluorocopolymer matrix has a melt flow rate (MFR) of 10 to 30 g / 10 min.
24. The laminate according to any one of the preceding claims, wherein the perfluorocopolymer matrix has a solder float resistance of at least 10 seconds at 288°C.
25. The laminate according to any one of the preceding claims, wherein the L-glass has a particle size of less than 100 g / m 2 The basis weight.
26. The laminate of claim 25, wherein the L-glass fabric has a basis weight of less than 50 g / m 2 .
27. The laminate according to any one of the preceding claims, wherein the L-glass fabric has a thickness of 10 to 100 μm.
28. The laminate according to claim 27, wherein the L-glass fabric has a thickness of 10 μm to 30 μm.
29. The laminate of any one of the preceding claims wherein the L-glass fabric comprises an aminosilane or methacrylate silane surface chemistry treatment.
30. The laminate of any one of the preceding claims, wherein the L-glass fabric comprises a plasma treated or corona treated L-glass fabric.
31. A laminate according to any one of the preceding claims, wherein the L-glass fabric is impregnated with a fluoropolymer.
32. The laminate of any one of the preceding claims, wherein the L-glass fabric comprises a fluoropolymer coating.
33. The laminate of any one of the preceding claims wherein the L-glass fabric is pre-treated with a fluoropolymer treating agent prior to incorporation into the laminate.
34. The laminate of any one of the preceding claims, wherein the dielectric substrate comprises 5 to 20 volume percent of the L-glass fabric and 80 to 95 volume percent of the perfluorocopolymer matrix.
35. The laminate according to any one of the preceding claims, wherein the L-glass fabric has a water contact angle of 0° to 60°.
36. A laminate according to any one of the preceding claims, wherein the additive material comprises inorganic particles.
37. The laminate of claim 36, wherein the inorganic particles comprise particles of cerium oxide, titanium dioxide, silicon dioxide, barium titanate, calcium titanate, or zinc oxide.
38. A laminate according to any one of the preceding claims, wherein the additive material comprises a thermosetting polymer.
39. A laminate according to any one of the preceding claims, wherein the additive material is present in the perfluorocopolymer matrix at a volume percentage of less than 2%.
40. The laminate according to any one of the preceding claims, wherein the additive material is uniformly dispersed throughout the perfluorocopolymer matrix.
41. A laminate according to any one of the preceding claims, wherein the conductive coating is provided on two opposing surfaces of the dielectric substrate.
42. A laminate according to any one of the preceding claims, wherein the conductive plating comprises copper foil.
43. The laminated product of claim 42, wherein the copper foil is disposed on the surface of the dielectric substrate by a lamination process.
44. A laminate according to any preceding claim, wherein the conductive coating has a thickness of less than 72 μm.
45. The laminate according to claim 44, wherein the thickness of the conductive plating layer is 5 μm to 18 μm.
46. A laminate according to any one of the preceding claims, wherein the conductive coating has a root mean square (RMS) roughness of less than 1 μm.
47. The laminate of claim 46, wherein the conductive coating has an RMS roughness of less than 0.5 μm.
48. A printed circuit board, comprising: The laminate according to any one of the preceding claims, A conductor pattern is formed in the conductive plating layer.
49. The printed wiring board of claim 48, wherein a through hole is defined through the thickness of the laminate; and comprising a copper film that plates the through hole.
50. A multilayer printed circuit board, comprising: A multi-layer laminate structure comprising a plurality of printed wiring boards according to claim 48 or 49.
51. The multilayer printed wiring board of claim 50, comprising a thermoplastic adhesive disposed between adjacent printed wiring boards in the laminate structure.
52. The multilayer printed wiring board of claim 51, wherein the thermoplastic adhesive bonds at a temperature of 0°C to 200°C below the melting point of the perfluorocopolymer matrix.
53. The multilayer printed wiring board of claim 52, wherein the thermoplastic adhesive bonds at a temperature of 0°C to 50°C below the melting point of the perfluorocopolymer matrix.
54. The multilayer printed wiring board of claim 50, comprising a thermosetting adhesive disposed between adjacent printed wiring boards in the laminated structure.
55. The multilayer printed wiring board according to claim 54, wherein the thermosetting adhesive is cured at a temperature of 150°C to 250°C.
56. A multilayer printed wiring board according to any one of claims 5048 to 55, wherein a through hole is defined through at least a portion of the thickness of the multilayer printed wiring board; and includes a copper film that plates the through hole.
57. An antenna capable of being used with a 5G communications network, the antenna comprising: A printed wiring board according to any one of claims 50 to 56.
58. A method for manufacturing a multilayer printed wiring board, the method comprising: forming a conductor pattern in the conductive plating layer of each of a plurality of laminates according to claim 1 to form a corresponding printed wiring board; as well as A plurality of printed wiring boards are laminated to form a multi-layer laminate structure.
59. The method of claim 58, wherein laminating the plurality of printed wiring boards comprises adhering adjacent printed wiring boards using a thermoplastic adhesive.
60. The method of claim 59, comprising bonding the thermoplastic adhesive at a temperature of 0°C to 200°C below the melting point of the perfluorocopolymer matrix.
61. The method of claim 60, comprising bonding the thermoplastic adhesive at a temperature of 0°C to 50°C below the melting point of the perfluorocopolymer matrix.
62. The method of claim 58, wherein laminating the plurality of printed wiring boards comprises using a thermosetting adhesive to adhere adjacent printed wiring boards.
63. The method of claim 62, comprising curing the thermosetting adhesive at a temperature of 150°C to 250°C.
64. A method according to any one of claims 58 to 63, comprising defining a through hole through at least a portion of the thickness of the multilayer laminate structure.
65. The method of claim 64, comprising defining the through-holes in an ultraviolet laser drilling process.
66. A method of making a laminated product, the method comprising: A layered article is formed, the layered article comprising: A first polymer film and a second polymer film, each film comprising: a perfluoro copolymer matrix comprising a fluorinated perfluoro copolymer and a non-fluorinated perfluoro copolymer, and an additive material capable of absorbing ultraviolet light, An L-glass fabric disposed between the first polymer film and the second polymer film; and a conductive plating layer disposed in contact with the first film; and Heat and pressure are applied to the layered article to form the laminate.
67. The method of claim 66, wherein the fluorinated perfluoro copolymer comprises a fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer and the non-fluorinated perfluoro copolymer comprises a non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer.
68. The method of claim 66 or 67, wherein applying heat and pressure to the layered article comprises compressing the layered article in a heated press plate.
69. The method of any one of claims 66 to 68, wherein applying heat and pressure to the layered article comprises processing the layered article in a roll-to-roll lamination process.
70. The method of any one of claims 66 to 69, wherein applying heat and pressure to the layered article comprises applying a temperature to the layered article that is 10°C to 30°C above the melting point of the perfluorocopolymer matrix.
71. The method of any one of claims 66 to 70, wherein applying heat and pressure to the layered article comprises applying a temperature of 300°C to 400°C to the layered article.
72. The method of any one of claims 66 to 71, wherein applying heat and pressure to the layered article comprises applying a pressure of 200 psi to 1000 psi to the layered article.
73. The method of any one of claims 66 to 72, comprising forming the first film and the second film in a melt processing and extrusion process.
74. The method of claim 73, wherein forming the first film and the second film comprises mixing the fluorinated perfluoro copolymer and the non-fluorinated perfluoro copolymer.
75. The method of claim 74, comprising dispersing an additive material in the fluorinated perfluorocopolymer prior to mixing the fluorinated perfluorocopolymer and the non-fluorinated perfluorocopolymer.
76. The method of any one of claims 66 to 75, comprising treating the L-glass fabric with a fluoropolymer treating agent.
77. The method of claim 76, wherein treating the L-glass fabric with a fluoropolymer treatment comprises coating the L-glass fabric with a fluoropolymer coating.
78. The method of claim 77, wherein coating the L-glass fabric with a fluoropolymer coating comprises coating the L-glass fabric in a solution coating process.
79. The method of claim 77 or 78, wherein coating the L-glass fabric with a fluoropolymer coating comprises depositing fluoropolymer particles on a surface of the L-glass fabric.
80. The method of any one of claims 66 to 79, wherein each polymer film comprises a first layer and a second layer, the first layer comprising the fluorinated perfluoro copolymer and the non-fluorinated perfluoro copolymer, the second layer comprising the non-fluorinated perfluoro copolymer, and wherein each second layer is disposed in contact with a quartz fabric and each second layer is disposed in contact with the conductive coating.
